The Adaptive Internet Application for Interpretation of the Transformer Oil Gas Chromatographic Analysis Results - Polužanski, Vladimir; Bojić, Dragan; Miladinović, Nikola; Lukić, Jelena; Milosavljević, Srđan (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
This paper describes an adaptive Internet application for the interpretation of the transformer oil gas chromatographic analysis results. The first version of the application is developed by following an evolutionary software development concept. The most important software development risks and the appropriate solutions are described. An open-source web framework named Bootstrap is used for an application implementation. The application is developed by using ASP.NET and MS SQL server.